NORMATIVITY OF SCIENTIFIC LAWS (I): TWO KINDS OF NORMATIVITY. - Mets, Ave (Problems / Problemos, 2018)
This article presents the results of a broader research project which aims to argue for the normativity of scientific laws. Usually scientific laws are regarded as descriptive, which contrasts them to prescriptive norms. To show their normativity, I utilize the logical account of explicitly normative systems by Carlos Alchourrón and Eugenio Bulygin (1971). I identify the characteristic elements of normativity and analyse accounts of implicit normativity in science using those terms to show the affinities of explicit and implicit normativities. The research project continues with the substantiation of the normativity of scientific laws in detail and the results will be presented in Normativity of Scientific Laws (II) (Mets 2018).